Development of 3D Microvascular Networks Within Gelatin Hydrogels Using Thermoresponsive Sacrificial Microfibers - Lee, Jung Bok; Wang, Xintong; Faley, Shannon; Baer, Bradly; Balikov, Daniel A.; Sung, Hak-Joon; Bellan, Leon M. (Advanced healthcare materials, 2016)
A 3D microvascularized gelatin hydrogel is produced using thermoresponsive sacrificial poly(N‐isopropylacrylamide) microfibers. The capillary‐like microvascular network allows constant perfusion of media throughout the thick hydrogel, and significantly improves the viability of human neonatal dermal fibroblasts encapsulated within the gel at a high density.